La Castañeda Insane Asylum : Narratives of Pain in Modern Mexico - Rivera Garza, Cristina, 1964- (Book collections on Project MUSE., 2020)
"An inside view of the workings of La Castañeda General Insane Asylum-a public mental health institution founded in Mexico City in 1910 only months before the outbreak of the Mexican Revolution"--